Effffectt off experiimenttalllly iinffecttiion llayer chiickens wiitth lliistteriia monocyttogenes iin iisollattiion off bactteriia ffrom organs and egg componentts: Fariis A.. All--Obaiidii ,, Metthaq G.. All--Rubaiiey - Al-Obaidi, Faris A. (The Iraqi Journal of Veterinary Medicine, 2010)
The objjectt of tthiis sttudy was focused on ttransmiissiion of Liitteriiamonocyttogenes tthrough llayer body ,, tthe rolle of tthiis biirds iin tthe spread of tthiis bactteriiaand tthe effectt of experiimenttalllly iinfecttiion dose of tthe llayer oralllly on bactteriiatransmiitttted tto eggs ,,egg componentts and iintternall organs .. A ttottall of 45 llayer werediisttriibutted iintto tthree groups and each group tto tthree replliicattes (15 llayer per replliicatte)cosnsiistted of T1 (conttroll group free of iinfecttiion) ,, T2 and T3 were orallllyexperiimenttalllly iinfectted by 1x105 and 1x1010 (CFU \\ mll \\ hen of L.. monocyttogenes ..Resulltts iindiicatted tthatt ..L.. monocyttogenes were iisollatted from ovary,, oviiductt,,utterus,, proventtiicullous,, giizzard,, heartt,, lliiver,, splleen,, iinttesttiine and cecum aftter 3,, 6,, 9,,15and 21 days of experiimenttalllly iinfecttiion and tthe llowestt iisollatted ratte from T2 groupcompared wiitth T3 group ..Allso ,, tthe bactteriia were iisollatted from egg shellll ,, shellllmembrane and egg allbumen of eggs produced from T2 and T3 group llayers aftter 3,, 6,,9,, days and tthe iisollattiion ratte decreased gradualllly from tthe tthree componentts of ttheegg aftter 15 days ,,when as tthe iisollattiion from yollk membrane ,, yollk flluiid and germiinallcellll aftter 6 days of iinfecttiion and decreased gradualllly aftter 21 days ..